LINGUISTIC ECONOMY AS A WAY OF OPTIMISATION COMMUNICATIVE INTERACTION (BASED ON THE MATERIAL OF GERMAN LINGUOCULTURE) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-3-62-71Linguistic economy is one of the ways how to optimise the communication process, aimed at achieving successful communication. As a result of a pragmalinguistic analysis of the functioning of the principle of linguistic economy, the main means of optimization used by the Germans in SMS communication were identified at all levels of the language system. The phonemic level is represented by cases of reduction of final vowels and consonants. At the morphemic level, truncating of word-forming and inflectional affixes is used. Lexical optimization methods include univerbation, abbreviation, and the use of borrowed words. In turn, ellipses are syntactic means of linguistic economy.Key words: principle of linguistic economy, means of linguistic economy, optimization, SMS communication